2013
DOI: 10.1097/bot.0b013e3182517e1c
|View full text |Cite
|
Sign up to set email alerts
|

Short-Term Physical and Mental Health Outcomes for Combat Amputee and Nonamputee Extremity Injury Patients

Abstract: Prognostic Level II. See Instructions for Authors for a complete description of levels of evidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 11 publications
0
28
1
Order By: Relevance
“…In one study, Melcer et al found that late amputees and limb salvage patients had significantly higher rates of PTSD compared to early amputees and that late amputees had significantly higher rates of most psychological diagnoses than limb salvage patients [18]. Other studies have also shown that limb-salvage patients had significantly higher rates TBI and PTSD than amputees after sustaining lower extremity trauma but that late amputees have the highest number of total mental health conditions [15,34]. As with the presence of complications, this data seem to suggest that it is the injury, and not the treatment, that impacts an injured service member's mental reaction to his or her injury.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations
“…In one study, Melcer et al found that late amputees and limb salvage patients had significantly higher rates of PTSD compared to early amputees and that late amputees had significantly higher rates of most psychological diagnoses than limb salvage patients [18]. Other studies have also shown that limb-salvage patients had significantly higher rates TBI and PTSD than amputees after sustaining lower extremity trauma but that late amputees have the highest number of total mental health conditions [15,34]. As with the presence of complications, this data seem to suggest that it is the injury, and not the treatment, that impacts an injured service member's mental reaction to his or her injury.…”
Section: Discussionmentioning
confidence: 93%
“…possible that late amputees experience the majority of their complications within the acute and sub-acute periods following late amputation evaluated by this study [15,18]. In this sense, data extracted from a relatively short interval of follow-up may overstate the impact of complications among late amputees and that the incidence of complications does, in fact, recede with time.…”
Section: Mental Health Conditionmentioning
confidence: 88%
See 2 more Smart Citations
“…Posttraumatic stress disorder and traumatic brain injury were also very impactful disabling conditions. While such conditions are quite common among those injured in combat, it should be recognized that such a condition is likely to hamper the rehabilitative efforts of these injured servicemembers [23]. As such, rehabilitative efforts for these servicemembers should include some aspect that deals directly with these conditions in order to maximize their outcomes.…”
Section: Figurementioning
confidence: 99%